Long known, brand new, and possibly threatened: a new species of watersnake of the genus Helicops Wagler, 1828 (Serpentes; Xenodontinae) from the Tocantins-Araguaia River Basin, Brazil - Moraes-Da-Silva, Antonio; Amaro, Renata Cecília; Nunes, Pedro M. Sales; Rodrigues, Miguel Trefaut; Curcio, Felipe Franco (Zootaxa, 2021)
We describe a new species of watersnake of the genus Helicops from the Tocantins-Araguaia River Basin based on characters of coloration and hemipenial morphology, also corroborated by a molecular phylogenetic analysis including 18 terminals of 10 additional congeners. The new species superficially resembles the spotted-patterned He. leopardinus, but differs from it in exhibiting dorsal spots fused into irregular bands, and a unique hemipenial structure with two pairs of distinctly enlarged basal spines. In addition, despite the superficial resemblance of color pattern, our genetic evidence indicates that the new species does not belong to the He. leopardinus radiation, representing the sister group of a component including terminals of this species, He. modestus, and He. infrataeniatus. Finally, we discuss the apparent restriction of the new species to the Tocantins-Araguaia Basin with focus on vicariant processes that may have promoted its differentiation, as well as on the conservation challenges in an area severely affected by anthropic impacts associated with the rapid expansion of hydroelectric and agricultural sectors in the Brazilian Cerrado.